Scenario of mental health in Bangladesh: A signature glimpse - Rozario, Lipy Gloria; Islam, Shaheen (Dhaka University Journal of Biological Sciences, 2022)
The study aims to gain primary evidences on the mental health condition of Bangladesh. A quantitative survey instrument was applied on 982 respondents from Dhaka, Chittagong, and Rajshahi divisions in Bangladesh. It included adult sample, aged above 18 years from different hospitals, universities and organizations. 51.7% of the respondents were male and rest 48.9% female. The survey focused on knowledge, attitude and behavior related to mental health. This paper presents the behavioral manifestation of mental health condition. From the description of different psychological problems the responders encounter in their life, depression (69.5%) was identified as the highest manifested mental health issue followed by anxiety (66.8%) and study-related issues (64.5%). Notable percentage had experience of trauma (28.0%), and abuse (19.2% physical abuse and 10.1% sexual abuse). Suicidal ideation was found to be present in 19.8% of the respondents. Significant gender differences towards male were found for problem with study, anger, romantic relation, eating, and substance abuse. Females had significantly higher experience of sexual abuse. Similar significant regional difference were noted for several behavioral indicators of mental health; Dhaka being the highest prevailing region. It was found to be true specifically for suicidal thoughts and attempts. This study reestablished the alarming situation of mental health existing among the people in Bangladesh which call forth urgent action to address the most vital aspect of health through psychological assistance. Dhaka Univ. J. Biol. Sci. 30(3 CSI): 405-416, 2022 (June)